2016
DOI: 10.1177/1076029616637185
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urinary Orosomucoid in Young Patients With Type 1 Diabetes

Abstract: Orosomucoid is an acute-phase serum protein that is upregulated in urine samples of patients with diabetic nephropathy. We assessed serum and urinary orosomucoid levels in children and adolescents with type 1 diabetes and their relation to microvascular complications and carotid intima-media thickness (CIMT). Sixty patients with type 1 diabetes were divided into 2 groups according to the presence of microvascular complications and compared with 60 healthy controls. High-sensitivity C-reactive protein (hs-CRP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Previous studies showed excessive u-ORM excretion in several chronic and acute inflammatory conditions 17 - 20 . Moderate elevation of u-ORM levels were found in diabetes mellitus and also in cardiovascular diseases, presumably associated with chronic low grade inflammation, endothelial dysfunction and oxidative stress which are also pathophysiologic factors in psoriasis 8 , 22 , 27 - 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed excessive u-ORM excretion in several chronic and acute inflammatory conditions 17 - 20 . Moderate elevation of u-ORM levels were found in diabetes mellitus and also in cardiovascular diseases, presumably associated with chronic low grade inflammation, endothelial dysfunction and oxidative stress which are also pathophysiologic factors in psoriasis 8 , 22 , 27 - 30 .…”
Section: Discussionmentioning
confidence: 99%
“…ORM exhibits many biological activities, including modulating immunity, binding and carrying drugs, maintaining the capillary barrier and acting as a disease marker. 17 The role of ORM in cancer, 18 , 19 , 20 cardiovascular diseases 21 , 22 and energy metabolism 23 was revealed recently. We previously reported that ORM was significantly elevated in the sera, liver and muscle tissues of fatigued rodents (for example, sleep-deprivation, forced swimming and treadmill-running models) and the sera of chronic fatigue syndrome patients.…”
Section: Introductionmentioning
confidence: 99%
“…ORM1 is assumed to play a role in induction of cancer development and is involved in regulation of angiogenesis (Muhammad et al, 2017). We based our study of ORM in DM2 on published findings of relation between ORM and DM1 (El-Beblawy et al, 2016). Our data showed that evaluation of serum levels of ORM and its dynamics related to DM complication is valuable.…”
Section: Discussionmentioning
confidence: 92%
“…Diabetic patients are endangered by various complications, influencing the quality of their life functions. Diabetic Retinopathy (DR) holds the most common complications of DM with current prevalence reaching more than 10 million wordwide (El-Beblawy et al, 2016). Regulation of immune functions and control of inflammatory processes are decisive in maintaining normal retinal functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation